Power Generation Infrastructure and its Effect on Electric Energy Consumption: Context in Indonesia, 2013–2020 - Hasid, Zamruddin; Mire, Muhammad Saleh; Rochaida, Eny; Wijaya, Adi (International Journal of Energy Economics and Policy, 2023)
For centuries, humans have continued to deplete natural resources. The transportation sector is claimed to be the main culprit in wasting fossil energy. The purpose of this study is to investigate the impact of Fossil Fuels Electricity (FFE), Wind Electricity (WE), Solar Electricity (SE), Hydroelectricity (H), and Geothermal Electricity (GE) on Access to Electricity (AE) in Indonesia. The collection of data obtained from the Global Economy report, processed using time-series regression. Empirical testing clarifies that the increase in the variables of FFE, WE, SE, H, and GE, has increased AE in the short term. The more FFE, WE, SE, H, and GE increase 1 percent, the more AE increases in the long run. During 2013–2020, FFE as a variable that has a dominant effect on AE, where the nature of this energy is very limited, the frequency of its use is considered. Apart from the role of FFE which is crucial for basic human needs, it is necessary to restructure the rules that regulate, monitoring, and revitalize power generation systems based on natural gas, oil, and coal.